Association of statin pretreatment with collateral circulation and final infarct volume in acute ischemic stroke patients: A meta-analysis. (March 2019) - Malhotra, Konark; Safouris, Apostolos; Goyal, Nitin; Arthur, Adam; Liebeskind, David S.; Katsanos, Aristeidis H.; Sargento-Freitas, João; Ribo, Marc; Molina, Carlos; Chung, Jong-Won; Bang, Oh Young; Magoufis, Georgios; et al.
Abstract: Background and aims: Statin pretreatment (SP) is associated with improved outcomes in acute ischemic stroke (AIS) patients. Collateral circulation status and final infarct volume (FIV) are independent predictors of functional outcome in AIS. Methods: We sought to evaluate the association of SP with collateral circulation and FIV in AIS patients. We used a random-effects model for all the analyses, and pooled standardized mean differences (SMDs) and odds ratios (OR) on the FIV and collateral status according to SP history, respectively. Results: We identified 9 eligible studies (1186 AIS patients). History of SP was associated with lower FIV (SMD = 0.25, 95%CI: 0.07–0.42, p  = 0.005) compared to negative history of SP. A trend towards good collateral scores was observed in the SP group (OR = 1.45; 95% CI, 0.92–2.29, p  = 0.11). Subgroup analysis demonstrated reduced FIV among atherosclerotic stroke patients with history of SP (SMD = 0.49; 95% CI, 0.19–0.80, p  = 0.001). Conclusions: SP appears to be associated with decreased FIV, especially in atherosclerotic AIS. Highlights: Collateral circulation status and final infarct volume (FIV) are independent outcome predictors after an AIS. We evaluated the association of statin pretreatment (SP) on collateral circulation and FIV in AIS patients. SP was associated with lower FIV compared to no SP, especially in atherosclerotic AIS. A trend towards good collateral scores was observed in the SP group. SP appears to be associated with decreased FIV after AIS, possibly due to more favorable collateral circulation.